Respiratory Support for Pharmacologically Induced Hypoxia in Neonatal Calves - C. G. Donnelly; C. T. Quinn; S. G. Nielsen; S. L. Raidal (Veterinary Medicine International)
Practical methods to provide respiratory support to bovine neonates in a field setting are poorly characterised. This study evaluated the response of healthy neonatal calves with pharmacologically induced respiratory suppression to nasal oxygen insufflation and to continuous positive airway pressure (CPAP) delivered via an off-the-shelf device. Ten calves were randomised to receive either nasal oxygen insufflation (Group 1, n=5) or CPAP (Group 2, n=5) as a first treatment after induction of respiratory depression by intravenous administration of xylazine, fentanyl, and diazepam. Calves received the alternate treatment after 10 minutes of breathing ambient air. Arterial blood gas samples were obtained prior to sedation, following sedation, following the first and second treatment, and after breathing ambient air before and after the second treatment. Oxygen insufflation significantly increased arterial oxygen partial pressure (PaO2) but was also associated with significant hypercapnia. When used as the first treatment, CPAP was associated with significantly decreased arterial partial pressure of carbon dioxide but did not increase PaO2. These results suggest that the use of CPAP may represent a practical method for correction of hypercapnia associated with inadequate ventilation in a field setting, and further research is required to characterise the use of CPAP with increased inspired oxygen concentrations.